Epigenomic identification of vernalization cis-regulatory elements in winter wheat - Yanhong Liu; Pan Liu; Lifeng Gao; Yushan Li; Xueni Ren; Jizeng Jia; Lei Wang; Xu Zheng; Yiping Tong; Hongcui Pei; Zefu Lu (Genome Biology, 2024)
Abstract Background Winter wheat undergoes vernalization, a process activated by prolonged exposure to low temperatures. During this phase, flowering signals are generated and transported to the apical meristems, stimulating the transition to the inflorescence meristem while inhibiting tiller bud elongation. Although some vernalization genes have been identified, the key cis-regulatory elements and precise mechanisms governing this process in wheat remain largely unknown. Results In this study, we construct extensive epigenomic and transcriptomic profiling across multiple tissues—leaf, axillary bud, and shoot apex—during the vernalization of winter wheat. Epigenetic modifications play a crucial role in eliciting tissue-specific responses and sub-genome-divergent expressions during vernalization. Notably, we observe that H3K27me3 primarily regulates vernalization-induced genes and has limited influence on vernalization-repressed genes. The integration of these datasets enables the identification of 10,600 putative vernalization-related regulatory elements including distal accessible chromatin regions (ACRs) situated 30Kb upstream of VRN3, contributing to the construction of a comprehensive regulatory network. Furthermore, we discover that TaSPL7/15, integral components of the aging-related flowering pathway, interact with the VRN1 promoter and VRN3 distal regulatory elements. These interactions finely regulate their expressions, consequently impacting the vernalization process and flowering. Conclusions Our study offers critical insights into wheat vernalization’s epigenomic dynamics and identifies the putative regulatory elements crucial for developing wheat germplasm with varied vernalization characteristics. It also establishes a vernalization-related transcriptional network, and uncovers that TaSPL7/15 from the aging pathway participates in vernalization by directly binding to the VRN1 promoter and VRN3 distal regulatory elements.